Safety Implications of Standardized Continuous Quality Improvement Programs in Community Pharmacy. (June 2013) - Boyle, Todd A.; Ho, Certina; MacKinnon, Neil J.; Mahaffey, Thomas; Taylor, Jeffrey M.
Standardized continuous quality improvement (CQI) programs combine Web-based technologies and standardized improvement processes, tools, and expectations to enable quality-related events (QREs) occurring in individual pharmacies to be shared with pharmacies in other jurisdictions. Because standardized CQI programs are still new to community pharmacy, little is known about how they impact medication safety. This research identifies key aspects of medication safety that change as a result of implementing a standardized CQI program. Fifty-three community pharmacies in Nova Scotia, Canada, adopted the SafetyNET-Rx standardized CQI program in April 2010. The Institute for Safe Medication Practices (ISMP) Canada's Medication Safety Self-Assessment (MSSA) survey was administered to these pharmacies before and 1 year into their use of the SafetyNET-Rx program. The nonparametric Wilcoxon signed-rank test was used to explore where changes in patient safety occurred as a result of SafetyNETRx use. Significant improvements occurred with quality processes and risk management, staff competence, and education, and communication of drug orders and other information. Patient education, environmental factors, and the use of devices did not show statistically significant changes. As CQI programs are designed to share learning from QREs, it is reassuring to see that the largest improvements are related to quality processes, risk management, staff competence, and education.